2010
DOI: 10.4314/biokem.v19i2.56429
|View full text |Cite
|
Sign up to set email alerts
|

Some liver function indices and blood parameters in T. <i>brucei</i>-infected rats treated with honey

Abstract: Honey has been reported to clear infection through a number of properties including boosting the immune system, its anti-inflammatory action, antioxidant activity and stimulation of cell growth. Anaemia and serum biochemical changes are common features of African trypanosomosis. We investigated whether honey has protective effect on some liver functions and blood parameters affected by trypanosome infection. The serum albumin concentration in infected untreated rats increased significantly (p<0.05) compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
(5 reference statements)
2
5
2
Order By: Relevance
“…The statistically non-significant difference recorded across the groups for WBC, neutrophil and monocyte counts in this study, suggests that T. brucei brucei (Federe isolate) infection may have had a mild immunosuppressive effect in the Nigerian donkeys (Equus asinus) studied. This contrasts with findings in studies on T. brucei infection in rats, where significant changes in total leucocyte counts were recorded post infection and treatment (29). Therefore, there is the need to investigate the type of immune response exhibited by these Nigerian donkeys following infection with T. brucei brucei (Federe isolate) to understand the influence of this infection on the immune system of these species.…”
Section: Trypanosoma Brucei Brucei (Federe Isolate)contrasting
confidence: 47%
“…The statistically non-significant difference recorded across the groups for WBC, neutrophil and monocyte counts in this study, suggests that T. brucei brucei (Federe isolate) infection may have had a mild immunosuppressive effect in the Nigerian donkeys (Equus asinus) studied. This contrasts with findings in studies on T. brucei infection in rats, where significant changes in total leucocyte counts were recorded post infection and treatment (29). Therefore, there is the need to investigate the type of immune response exhibited by these Nigerian donkeys following infection with T. brucei brucei (Federe isolate) to understand the influence of this infection on the immune system of these species.…”
Section: Trypanosoma Brucei Brucei (Federe Isolate)contrasting
confidence: 47%
“…The Automated Haematologic Analyzer (Sysmex, KX-21, Japan) was used to analyse the haematological parameters of red blood cells (RBC), haemoglobin (Hb), packed cell volume (PCV), Mean corpuscular haemoglobin (MCH), mean corpuscular haemoglobin concentration (MCHC), large unstained cell (LUC), red cell width coefficient of variation (RDW-CV), white blood cell (WBC), mean platelet volume (MPV), platelet distribution width (PDW) and platelets. The levels of other parameters were determined as described for bilirubin (total and conjugated) [22] , total protein [23] , albumin [24] , globulin, sodium, calcium and potassium [25], whereas the activities of ALT and AST, GGT and ALP were determined using standard methods [26][27][28] .…”
Section: Determination Of Biochemical Parametersmentioning
confidence: 99%
“…Therefore the significant increase (P<0.05) in the level of albumin and bilirubin in the serum indicates damage to the liver, which is the site of synthesis of albumin. Moreso since bilirubin is transported to the liver bound to albumin, high plasma conjugated bilirubin concentration indicates impaired hepatic excretory function (Thapa and Walia, 2007;Mayne, 1994;Ekanem and Yusuf, 2007). Though over production and, or over excretion of bilirubin are known causes of high bilirubinemia (Kaplan 1987, Yakubu et al, 2012, it is more probable and arguable to link the observed increase in the parameters investigated in the present study to hepatocellular damage caused by administration of potassium bromate.…”
Section: Discussionmentioning
confidence: 66%
“…Its level may therefore be used as a measure to assess the synthetic function of the liver (Mayne, 1994;Ekanem and Yusuf, 2007). Therefore the significant increase (P<0.05) in the level of albumin and bilirubin in the serum indicates damage to the liver, which is the site of synthesis of albumin.…”
Section: Discussionmentioning
confidence: 99%